Loss of adhesion impairs invasiveness and cell survival, contributing to the antimetastatic effect of cysteine proteases from Vasconcella cundinamarcensis in melanoma - Dalton Dittz; Isabela Paula Nunes; Hortência Maciel de Castro Oliveira; Gustavo Batista de Menezes; Carlos Edmundo Salas Bravo; Miriam Teresa Paz Lopes (Scientific Reports)
Abstract Based on available evidence showing the antitumoral/antimetastatic activity of the proteolytic fraction (P1G10) from Vasconcellea cundinamarcensis, we analyze possible mechanisms involved in the antimetastasic effect of this fraction and subfractions (CMS1, CMS2) after incubation with B16F10 melanoma cells in vitro and in vivo under sub-apoptotic conditions. The goal was to investigate potential mediators of the antitumoral/antimetastatic effect of P1G10 triggered before the onset of apoptosis. In B16F10 preincubated viable cells, it was observed changes in adhesion to ECM (extracellular matrix), reduced activity of metalloproteases and invasivity, reduction of pAkt and pErk mostly affecting the rate of lung metastasis in mice injected with B16F10 treated cells. In most of these assays the effects depend of the proteolytic activity of the fractions. Unexpectedly, the CMS2-IAA (CMS2 with proteolytically activity inhibited by iodoacetamide), enhanced pErk phosphorylation and increased procaspase-3 levels. The invasivity of B16F10 was impaired following incubation with the proteolytic fraction without affecting cell viability under the conditions analyzed. In conclusion, CMS2 reduces in vitro cell invasion and metastasis in murine melanoma B16F10.